The efficacy and cerebral mechanism of intradermal acupuncture for major depressive disorder: a study protocol for a randomized controlled trial - Wu, Xiaoting; Tu, Mingqi; Chen, Nisang; Yang, Jiajia; Jin, Junyan; Qu, Siying; Xiong, Sangsang; Cao, Zhijian; Xu, Maosheng; Pei, Shuangyi; Hu, Hantong; Ge, Yinyan; et al. (Frontiers in Psychiatry, 2023)
Background Major depressive disorder (MDD) has emerged as the fifth leading cause of years lived with disability, with a high prevalent, affecting nearly 4% of the global population. While available evidence suggests that intradermal acupuncture may enhance the effectiveness of antidepressants, whether its efficacy is a specific therapeutic effect or a placebo effect has not been reported. Moreover, the cerebral mechanism of intradermal acupuncture as a superficial acupuncture (usually subcutaneous needling to a depth of 1–2 mm) for MDD remains unclear. Methods A total of 120 participants with MDD will be enrolled and randomized to the waiting list group, sham intradermal acupuncture group and active intradermal acupuncture group. All 3 groups will receive a 6-week intervention and a 4-week follow-up. The primary outcome will be measured by the Hamilton Depression Rating Scale-17 and the secondary outcome measures will be the Self-Rating depression scale and Pittsburgh sleep quality index. Assessments will be conducted at baseline, 3 weeks, 6 weeks, and during the follow-up period. In addition, 20 eligible participants in each group will be randomly selected to undergo head magnetic resonance imaging before and after the intervention to explore the effects of intradermal acupuncture on brain activity in MDD patients. Discussion If the intradermal acupuncture is beneficial, it is promising to be included in the routine treatment of MDD. Clinical Trial Registration Clinicaltrials.gov, NCT05720637.